2018
DOI: 10.3102/0013189x18776975
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Sustained Implementation of a Universal Behavior Support Framework

Abstract: In this 3-year prospective study, we tested the extent to which school-, practice-, and district-level variables predicted sustained implementation for schools in various stages of implementation of school-wide positive behavioral interventions and supports (SWPBIS) Tier 1 (universal) systems. Staff from 860 schools in 14 U.S. states completed a research-validated measure of factors associated with sustained implementation of school interventions during Year 1 of this study. Analyses included multigroup struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…Prior work has demonstrated data-based decision making can contribute to improve team use of data and contribute positively to student outcomes (Team Implemented Problem-Solving; Horner et al, 2018). McIntosh and colleagues (2018) also found that Team Use of Data during the first year of implementation was one of the strongest predictors for sustained implementation of SWPBIS past 3 years.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Prior work has demonstrated data-based decision making can contribute to improve team use of data and contribute positively to student outcomes (Team Implemented Problem-Solving; Horner et al, 2018). McIntosh and colleagues (2018) also found that Team Use of Data during the first year of implementation was one of the strongest predictors for sustained implementation of SWPBIS past 3 years.…”
Section: Discussionmentioning
confidence: 80%
“…Listening to Staff Concerns is an activity that may help a coach build rapport or collect information to guide the problem-solving process. Team Action Planning has been identified as a factor sustaining SWPBIS implementation (McIntosh et al, 2018). Coaches could help school teams in long-range planning including scheduling staff development activities or periodic evaluations of Tier 1 SWPBIS systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the fourth year, the year of the survey, 16 of the 30 schools (53.3%) reported fidelity data, 10 of the 16 schools (62.5%) were at fidelity, and six of the 16 schools (37.5%) were below fidelity. For schools that reported using multiple Tier 1 implementation fidelity measures during each of the four study years, we used their score from the implementation fidelity measure with the strongest psychometric properties described in the order above (McIntosh et al, 2018). The SET was the most common measure to determine fidelity in Year 1 (21/25 = 84% of schools) and Year 2 (15/23 = 65.2% of schools).…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have identified school and district factors to be associated with the sustained implementation of SWPBIS practices. For example, McIntosh and colleagues (2018) recently identified factors at the school level, specifically Tier 1 implementation fidelity in Year 1 and school teams using data for decision making, to be significant predictors of sustained implementation of SWPBIS in Year 3. In another study using structural equation modeling with a sample of 217 schools, McIntosh and colleagues (2013) found district priority and district capacity building (i.e., district technical assistance) to be predictors of Tier 1 SWPBIS sustainability.…”
Section: Research On School-wide Positive Behavioral Interventions Anmentioning
confidence: 99%